THE STRATEGIC RATIONAL OF BANKING ACQUISITION IN EMERGING MARKET - Johan, Suwinto (Journal Economics & Business Atmajaya Indonesia, 2018)
The  purpose of the research is to study the determinants of  banks acquisitions in Indonesia over the period of 2004-2014. The banking industry is one of the fastest growing and well regulated industries during the last ten years. We analyzed seven financial ratios (current ratio, asset turnover, debt to equity ratio, return on asset, return on equity, earning before tax per revenue and earning after tax per revenue) determinants banks take over. This research used the binary Logit regression technique. The empirical results show that the determinants of bank targeted for all types of takeover are the current ratio. The higher current ratio, the higher possiblity be the target acquisitions. there is no significant of debt to equity ratio, asset turnonver, return on asset, return on equity, earning before tax per revenue and earning after tax per revenue as the determinants of the acquisition of banks in Indonesia.